PENERAPAN METODE FUZZY WEIGHTED PRODUCT (WP) DENGAN PEMBOBOTAN ENTROPY - Dwi Ispriyanti; Azizah Mulia Mawarni; Alan Prahutama; Tarno Tarno (Jurnal Statistika Universitas Muhammadiyah Semarang, 2020)
The government, through the Directorate General of Higher Education, Ministry of National Education seeks to allocate funds to provide scholarships to students who are economically unable to finance their education, and provide scholarships to students who have achievements. The provision of learning assistance in the form of scholarships was given to students in various universities including Diponegoro University. Scholarships awarded include Academic Achievement Achievement scholarships (PPAs) awarded to outstanding students and scholarships Student Learning Assistance (BBM) given to underprivileged students. In recruiting prospective PPA scholarship recipients, the selection committee applies several assessment criteria. The required assessment criteria are the GPA value, the parent's income, the championship achievement, the semester, the number of dependents, and the electric power. The PPA scholarship selection system has not been effective even though it has been with the help of a computer. So there is a need for decision-making methods in assisting selection. The method applied in selecting scholarship recipients is WP, with Entropy weighting method. Previously, the criteria value was changed to fuzzy numbers. Fuzzy Weighted Product (WP) method successfully selected PPA scholarship recipients with optimal results to help screening committee.